Do Financial Sector Reforms Lead to Financial Development? : Evidence from a New Dataset - Tressel, Thierry; Detragiache, Enrica (Washington, D.C. : International Monetary Fund, 2008)
This paper studies whether the policies that, over the past decades, liberalized bankingsystems around the world have resulted in deeper credit markets. To measure banking sectorreforms we use a new index that tracks policy changes in five separate areas for 91 countriesover 1973-2005. We find that reforms have led to financial deepening, but only in countrieswith institutions that place checks and balances on political power. We interpret this asevidence of a complementarity between financial sector reforms and political institutions thatprotect property rights. Other country characteristics do not seem to significantly influencethe effect of banking reforms on financial development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet